The Influence Of Lampungnese Ethnicity Accent On Dialect A To Lampungnese Students’ Pronunciation Ability At English Education Study Program - Anggi Okta Dinata (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
This research was a qualitative research. Multiple methods were used in this research. They were observation, interview, transcription, and documentary.After getting the data, there were some influences in segmental and suprasemental features. At the segmental features, it influenced some consonant and vowel sounds. Those consonant sounds were [v] and [f] sound became [p] sound,[th] sound became [t] sound,[z] sound became [s] sound,[ch] sound became [c] sound, and [ǰ] became [ng]. Meanwhile, at the vowel sounds influenced monophtongs and diphtongs. At monophtongs, they were[é] sound became [ə] sound, [ə] sound became [é] sound, and [ɪ] sound became [e] sound. Meanwhile at the diphtongs, it was [ei] sound became [e] sound. At the suprasegmental features, there were some influences on the words’ stress and intonation. Some words and sentences were given inappropriate stress and intonation. Those things happened for some reasons. They were the intensity time in using English, the difference in phonological system between English and Lampungnese language, the sociolinguistic factor, the learner’s age, and the learner’s attitude and personality.